2019
DOI: 10.1002/ecy.2800
|View full text |Cite
|
Sign up to set email alerts
|

Size dependency of patch departure behavior: evidence from granivorous rodents

Abstract: Citation: Cozzoli, F., V. Gjoni, and A. Basset. 2019. Size dependency of patch departure behavior: evidence from granivorous rodents. Ecology 100(10):Abstract. Individual size is a major determinant of mobile organisms' ecology and behavior. This study aims to explore whether allometric scaling principles can provide an underlying framework for general patterns of resource patch use. To this end, we used giving-up densities (GUDs), that is, the amount of resources remaining in a patch after a forager has quit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 111 publications
1
9
0
Order By: Relevance
“…We showed that the effect of bioturbators on cohesive sediment resuspension can be described by bioturbators' population metabolic rate, with minor variations across different bioturbation modalities. This finding is in-line with other studies showing that indicators based on community size structure, rather than on species-specific characteristics, can be used to describe functional ecological processes or patterns such as community interactions (McGill, et al, 2006) and structure (Gjoni, et al, 2017;Gjoni & Basset, 2018), resource exploitation (Basset, et al, 2012a;Cozzoli, et al, 2018b;Cozzoli, et al, 2019), species coexistence (Canavero, et al, 2014), habitat carrying capacity (Edgar, 1993) and ecological status (Mouillot, et al, 2006;Menezes, et al, 2010;Basset, et al, 2012b).…”
Section: Accepted Manuscript Conclusionsupporting
confidence: 91%
“…We showed that the effect of bioturbators on cohesive sediment resuspension can be described by bioturbators' population metabolic rate, with minor variations across different bioturbation modalities. This finding is in-line with other studies showing that indicators based on community size structure, rather than on species-specific characteristics, can be used to describe functional ecological processes or patterns such as community interactions (McGill, et al, 2006) and structure (Gjoni, et al, 2017;Gjoni & Basset, 2018), resource exploitation (Basset, et al, 2012a;Cozzoli, et al, 2018b;Cozzoli, et al, 2019), species coexistence (Canavero, et al, 2014), habitat carrying capacity (Edgar, 1993) and ecological status (Mouillot, et al, 2006;Menezes, et al, 2010;Basset, et al, 2012b).…”
Section: Accepted Manuscript Conclusionsupporting
confidence: 91%
“…The intrinsic inclination of larger foragers to leave the resource patch earlier because of their inherently greater readiness to perceive resource limitation sooner has been theoretically hypothesized (Holling 1992, Basset 1995) and empirically observed (Brown et al 1988, Kotler and Brown 1990, Bowers et al 1993, Vasquez 1996, Searle et al 2005, Stenberg and Persson 2006, Cozzoli et al 2018, 2019). In this study, we show that not only larger individuals, but also individuals of the same size and species but with higher standard metabolic rates, are more likely to abandon the resource patch earlier, rather than face increasing competition for the remaining resources (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Under conditions of resource abundance and without considering the effect of extrinsic factors such as the risk of predation (Ward et al 2000), vagile foragers tend to persist on a resource patch and to avoid energy‐expensive behaviours such as exploration, which are in contrast adopted when the resource becomes scarce (Killen et al 2007). Patch departure decisions have been observed to be related to individual body mass: larger organisms abandon a resource patch earlier and at a resource density that is still exploitable for small foragers (Brown et al 1988, Kotler and Brown 1990, Bowers et al 1993, Vasquez 1996, Searle et al 2005, Stenberg and Persson 2006, Cozzoli et al 2018, 2019). The size dependency of an animal's propensity to abandon resource patches may be due to a number of mechanisms acting in synergy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, following the exclusion of both generalist and specialist predators, the abundance of montane voles ( Microtus montanus ) increased [ 122 ]. Where predator presence was found to affect rodent prey abundance, reports have indicated that the effects may be complexly interrelated with habitat, existing rodent densities, season, individual species behavioral characteristics, and type of predator [ 122 , 124 , 125 , 126 ]. These potential interactions are difficult to tease apart, both conceptually and statistically, and their resolution will require intensive long-term studies in natural and managed field conditions.…”
Section: Discussionmentioning
confidence: 99%